2015
DOI: 10.1142/s0192415x1550055x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Epimedium Herb on the Inflammatory ResponseIn VitroandIn Vivo

Abstract: Epimedium Herb (EH) is a medicinal herb used in traditional Eastern Asia. In this study described, we investigated the biological effects of Epimedium Herb water extract (EHWE) on lipopolysaccharide (LPS)-mediated inflammation in macrophages and local inflammation in vivo. We also investigated the biological effects of EHWE on the production of inflammatory mediators, pro-inflammatory cytokines and related products, as well as nuclear factor κB (NF-κB) and mitogen-activated protein kinase (MAPK) activation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Meanwhile, some pharmacological studies of herbs also indicated that constituents of WLT could be helpful for alleviating neuropathy (Kou et al, 2013 ; Sun et al, 2016 ). A study showed that epimedium extract promotes peripheral nerve regeneration in rats (Oh et al, 2015 ). Another study showed icariin, a flavonoid glycosides extracted from epimedium herb, promoted the expression of nNOs after neural injury (Shindel et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some pharmacological studies of herbs also indicated that constituents of WLT could be helpful for alleviating neuropathy (Kou et al, 2013 ; Sun et al, 2016 ). A study showed that epimedium extract promotes peripheral nerve regeneration in rats (Oh et al, 2015 ). Another study showed icariin, a flavonoid glycosides extracted from epimedium herb, promoted the expression of nNOs after neural injury (Shindel et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA concentrations were measured using a NanoDrop ND-1000 spectrophotometer (NanoDrop Technologies, Wilmington, DE) and 3 μg RNA was reverse transcribed using 1 st Strand cDNA Synthesis kit (BioAssay Co.). Quantitative real-time PCR was performed using QuantStudio 6 Flex Real-Time PCR system (Thermo Scientific, Rockford, IL, USA) as described previously 40 . For each gene, the Ct values were normalized to those of β-actin and then presented as fold differences compared to untreated control cells.…”
Section: Methodsmentioning
confidence: 99%
“…Icaritin might also have the potential to modulate estrogen metabolism, because icaritin has been shown to compete with TCDD at the AhR (IC 50 ≈ 1 μ M) and to induce CYP1A1 ( Tiong et al, 2012 ). Moreover, investigations with a water extract of herba Epimedii demonstrated anti-inflammatory activities in macrophages as well as in an in vivo inflammation model ( Oh et al, 2015 ). The extract inhibited NF- κ B activation and thus reduced iNOS and subsequent NO formation as well as reduced IL-6 and IL-1 β .…”
Section: Botanicals For Breast Cancer Preventionmentioning
confidence: 99%